THE IMPACT OF YOUTH SUBCULTURE ON PERSONAL IDENTITY - Otamuratov , Rustam; Otamuratova , Sarvinoz (Scientific practical conference, 2025)
The article analyzes the unique characteristics of the personality traits and values ​​of representatives of youth subcultures, which are interpreted as one of the most relevant topics today, and analyzes the acceptance of subcultures in terms of their connection with personal identity.